Efeitos discursivos nas publicidades de cerveja - Oliveira, Francisco Santana de (2014)
The advertising is part of a process by which brands, institutions and people make use of techniques, means and strategies of communication to make determined ideia be consumed, or as a product, service or atitude. The advertising makes use of discourses involving use of associations where the sense is determined to and by the subject with base in the conditions of production that envolves the memory, the interspeech and the history. With base in this informations, this job search analyze new gestures of readout and interpretation of beers commercials in Brazil. This job will be basis in analysis of French Discourse (AD) founded by Pêcheux and broadly crafted by Brazilian authors like Orlandi and Indusky. The AD seeks to work the language as an element that delivers the functioning of sense by means of the acts of reading and interpretation. The analyzes are based on electronic ads seeking answers to some questions, from among them: How are formulated appeals in beer commercials used in advertising? The women are, or not, main appeal sales of the main brand of the product in Brazil? The Society lends symbolic values that result in new gestures of the reading in advertisements over time? How meaning effects are created in the advertisements? Were sellected four eletronics ads widely known to analyze the formation and the constitution of their meaning effects based on the conditions of production existing at any given time in the history. The commercials were broadcast on TV stations schedules's open, but which are now part of the public domain through the video site YouTube. Two commercials are part of a sequence of ads served in the early 2000s and the other two were commercial aired in the mid year 2013/14. The analysis of the corpus occurred by the formation of the videos frame by frame taking into account concepts affiliated with AD as: interspeech, production conditions, discursive memory, place, happening, ideology and meaning. The analysis showed that the brand resorted to certain production conditions thus appearing that, by means of effects of massed sense, would result in acts of readout widely collectivized. That is, the advertising, articulated in the discourse, work through the ideology of consumption and this is attributed to unconscious characteristics of the subject widespread for memory and heterogeneous discourse well as by means of the ideological formations so that certain ideological symbols fit certain senses. Thus it was possible to understand that no matter if the appeal of propagandistic language of the beer production involves the woman or the adventure with friends, what matters to the brandis the positioning of the ideological formations of the product for the consumer subject.